An Analysis On Students Ability in Translating From Indonesian To In English At The 2th Grade Of SMA Negeri 1 Kuantan Mudik - Alfina Darmis; Rosmanizar Rosmanizar; Helfianora Ofrita (LPPI Yayasan Almahmudi bin Dahlan, 2023)
The aim of this research was to know the students’ ability to translate the Indonesian texts into English at the second grade of SMA Negeri 1 Kuantan Mudik. The researcher used test as the instrument to collect the data. This test aimed to examine the ability to translate the paragraphs of the Indonesian texts into English, which the texts consisted of three genres of texts such us, descriptive, narrative, and recount text. Every genre of text consisted of a paragraph. The data was collected through descriptive qualitative research Qualitative research is an approach for exploring and understanding the meaning individuals or groups ascribe to a social or human problem. The participants were all classes at the The 2th Grade Of SMA Negeri 1 Kuantan Mudik and it consisted of 40 students as sample. The analysis of the data collected through test for students. The result of the research showed the dominant percentage of students’ ability in translating Indonesian texts into English texts was in recount text category, Research her found that total score of students’ ability in changing yes – no question of Indonesian to yes – no question English the average test average 84,52 , from 21 students who completed 20 students and students who did not complete as many as 1 child. This means that the increase in learning outcomes on this test is influenced by the increase in the teacher's ability in English so that students become motivated, enthusiastic, active and enthusiastic in working on the test questions that have been given and explain a little about the purpose of the test. So that students more easily understand the material that has been given to students. Based on the test results that have been given, students are very active and enthusiastic during the test process, and the test results of students have completed well individually Keyword: Translation ability, text, Qualitative research